Kinerja Perusahaan: Pengaruh Corporate Social Responsibility dan Pertumbuhan Pendapatan - Anita Anita; Dewi Anggreni (Jurnal Akuntansi Bisnis, 2021)
Indonesia is currently being hit by the coronavirus disease 2019 (COVID-19-19) pandemic, making the level of competition between companies more competitive to generate profits. This strongly encourages companies to look for ways to attract investors' attention in capital market. The purpose of this study is to analyse the effect of corporate social responsibility (CSR) disclosure and revenue growth on the firm performance of sustainable companies listed on the Indonesia Stock Exchange (IDX). This study will examine whether there is a relationship between CSR disclosure in sustainability reports and revenue growth on firm performance. CSR is measured by GRI-Standards. Firm performance is measured by return on assets (ROA), return on equity (ROE), return on invested capital (ROIC), and economic value added (EVA). A sample of 37 companies was obtained from purposive sampling method, in which companies listed on IDX must completely published sustainability reports during the 2016-2020 period. The analysis technique with panel-based data regression. The results of this research show that CSR disclosure in sustainability reports has a significant positive effect on firm performance (EVA). Revenue growth in sustainable companies also has a significant positive effect on firm performance (ROE).